Diagnostic and therapeutic approach of peritoneaopericardial diaphragmatic hernia in the dog - Moreira, Brunna Silva; Nakamura, Aline Medeiros [UNESP]; Alves, Aracelle Elisane; Dantas Mota, Francisco Claudio (Universidade Federal do Paraná, 2019)
Peritoneopericardial is an uncommon congenital malformation in dogs and cats, characterized by anomalous communication between the diaphragm and the pericardial sac, causing the translocation of the abdominal viscera to the inside of the pericardial sac. Its prognosis is favorable and the most indicated treatment is the surgical. This paper aims at describing the diagnosis and treatment process in a dog with PPDH. This paper shows a 2-years-old male Shih Tzu diagnosed with compensated peritoneopericardial diaphragmatic hernia (PPDH). A reduction of the herniated content, composed of liver, spleen, intestinal loops and omentum, in addition to simultaneous reconstruction of the diaphragm and pericardium with resolution of the congenital anomaly.
Abordagem diagnóstica e terapêutica de hérnia diafragmática peritoneopericárdica em cão
Keywords: Dog; Herniorrhaphy; Surgery